Global and Russian Market of Chemical Products: Key Trends of Development - J. O. Sizova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Chemical industry is one of the leading and most essential spheres of economy. The article studies specific features and makes a comparative analysis of chemical industry production in Russia and the world, analyzes the structure of trade turnover according to Clause 6 of the uniform goods nomenclature of the foreign economic activity in the Eurasian Economic Union. Key challenges and prospects of development of this industry were identified. To make a comparison the author studied international chemical industry including hundreds of companies working with prospecting, treatment and distribution of gases and with the development of the most complicated organic chemicals used for pharmaceutical preparations. Russian chemical industry possesses resource potential for development but current problems hinder its progress. The major reasons are the following: the shortage of Russian competitive chemical equipment, expensive renewal of existing outdated capacities. At the same time it is possible to mention a low level of research and technical and HR potential of the industry. The author proposes approaches to the development of home chemical industry to provide a growth in output and a rise in competitiveness of this sector of Russian economy on the global level.